The Strong Convex Compactness Property and C0-Semigroups on Some Hereditarily Indecomposable Banach Spaces - Dehici, Abdelkader (Sarajevo Journal of Mathematics, 2018)
In this paper, we study the strong convex compactness property on the hereditarily indecomposable Banach spaces denoted respectively by XGM and XAM constructed by T. Gowers and B. Maurey (1993) and Argyros-Motakis (2014). We prove in particular that the Bochner integral of a family of strictly singular operators is a strictly singular operator. Also, some properties of C0-semigroups defined on these Banach spaces are given.